Socio-political conflict and economic performance in Bolivia - Jose Luis Evia; Roberto Laserna; Stergios Skaperdas (Center for Economic Studies and ifo Institute (CESifo), 2008)
We examine how socio-political conflict in Bolivia has affected its economic performance since the 1970s. Such conflict includes strikes, demonstrations, road blockades, and conventional rent-seeking. Since conflict has costs, it diverts resources away from production, tends to reduce investment and could therefore reduce economic growth. We first review the characteristics of conflict in Bolivia using a unique data set. We then provide estimates of the direct costs of conflict and examine the relationship with economic performance using hypotheses derived from a simple model. In particular, we make a distinction between economic growth that is due to external factors - like changes in income due to movements in the terms of trade - and economic growth that is due to productive investment. Growth due to external factors tends to be positively related to conflict, whereas growth due to productive investment should be negatively related to conflict. Finally, we discuss how levels of conflict, economic performance, and governance might be related in Bolivia's recent history.
Keywords: D70; H10; O11; O54; 330; economic growth; property rights; governance; Sozialer Konflikt; Wirtschaftswachstum; Soziale Kosten; Eigentumsrecht; Good Governance; Bolivien